Characteristics of agricultural phosphorus migration in different soil layers on purple soil sloping cropland under natural rainfall conditions - Wang, Yi; Chen, Fangxin; Zhao, Huan; Xie, Deti; Ni, Jiupai; Liao, Dunxiu (Frontiers in Environmental Science, 2023)
Limited by the current monitoring and collection methods of subsurface flow data, the characteristics of phosphorus (P) migration loss in different soil layers on sloping cropland under natural rainfall conditions need to be clarified. In this study, a reliable U-trough collection method (UCM) was used to explore P migration losses in different purple soil layers (L0: surface, L1: 0-20 cm, L2: 20-40 cm, L3: 40-60 cm) for purple soil sloping cropland during a field monitoring campaign spanning two calendar years under natural rainfall conditions. The results suggested that the annual surface P loss load was 1.08 kg*ha -1 *yr -1 , where 92.1% was particulate P. The annual leaching loss load of total P from the L1 layer was 3.55 kg*ha -1 *yr -1 , where 74.2% and 10.5% were intercepted by the L2 and L3 layers, respectively, to increase the in situ soil P stocks. Only 15.3% of L1's annually leached P, and only half the surface P loss load (L0), was lost to underground water. Heavy rain events on the purple soils in the studied sloping cropland induced 43.9% of the annual surface P loss load. In contrast, 36.1%, 30.5% and 30.3% of P's eventual annual leached loss loads resulted from heavy, moderate, and torrential rain events, respectively. The maize season was the main period of surface and subsurface P migration loss. Due to the limitation of experimental conditions, the results of this experiment could not represent the soil phosphorus migration process in the natural purple slope farmland in nature, but it could partially represent the soil phosphorus migration in the newly cultivated purple sloping cropland in Chongqing.